Bioactive volatile compounds from Penicillium digitatum-infected apples: Oviposition attractants for yellow peach moth Conogethes punctiferalis (Lepidoptera: Crambidae) - Guo, Hong Gang; Miao, Shuang Zhen; Ai, Peng Peng; Zhang, Min Zhao; Yan, Zhe; Du, Yan Li (Frontiers in Sustainable Food Systems, 2023)
Plant-associated microbes critically shape the dynamics of plant- and insect-associated communities. In previous studies, we reported that the yellow peach moth Conogethes punctiferalis (YPM) preferred to Penicillium digitatum-infected apples (PDA) for oviposition. However, the underlying mechanisms remains unclear. In the present study, the behavioral and physiological experiments were conducted to determine how P. digitatum affects the oviposition selection of mated YPM females via altering host plant volatile organic compounds (VOCs). Mated YPM females were attracted to and laid more eggs on PDA than on fungi non-infected apples (NIA), mechanically damaged apples (MDA), and P. digitatum in potato dextrose agar medium (PPD). Four-arm olfactometer assays further confirmed that odors in PDA were responsible for the attractiveness of mated YPM females. PCA of the 38 VOCs revealed a clear separation of PDA from NIA, MDA, and PPD, including methyl 2-methylbutyrate, styrene, methyl caproate, butyl caprylate, and n-tetradecane that were specifically emitted by PDA. Moreover, when P. digitatum-induced specific VOCs in individual or synthetic blends consisting of methyl 2-methylbutyrate, butyl caprylate, or n-tetradecane were added to apples, a significant selection rate of mated YPM females choosing apples occurred, suggesting that these three specific VOCs acted as predominant olfactory signals for mated YPM females to PDA. Taken together, the microbe P. digitatum was an important driver of the interactions between YPMs and host plants by altering plant volatiles. These findings may form the basis for developing attractant baits for field trapping YPMs in the future.